Eksplorasi Nilai-Nilai Novel dalam Novel Janji Karya Tere Liye dan Relevansinya terhadap Pendidikan Agama Islam - Arafah, Azizah; Firman, Firman; Aswar, Nurul (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Islamic education plays a crucial role in shaping the character of young generations to become individuals with noble character and a deep understanding of Islamic values. However, the challenges of globalization demand creative approaches in delivering educational messages, one of which is through literary works such as novels. The novel Janji by Tere Liye was chosen as the object of this research because it contains religious, moral, social, cultural, and educational values that are relevant to Islamic education. This study aims to explore the values contained in the novel and analyze their relevance to Islamic education. The research method used is qualitative, with a library research approach and hermeneutic analysis. Data were collected through an in-depth reading of the novel Janji, then classified based on the values found in it. The analysis was carried out by identifying, reducing, and interpreting the text to discover connections between the novel’s values and the principles of Islamic education. The findings show that the novel Janji is rich in Islamic values, including aspects of aqidah (faith in Allah), akhlaq (honesty, patience, responsibility), and sharia (devotion in worship, fulfilling promises). These values are highly relevant to the goals of Islamic education in forming students with faith and noble character. In addition, the novel strengthens students' understanding of social and cultural values from an Islamic perspective. The implication of this research encourages educators to use literary works as alternative media in Islamic education, making the learning process more engaging and contextual.